Feedback of coastal marshes to climate change: Long‐term phenological shifts. Issue 12 (13th June 2019) - Mo, Yu; Kearney, Michael S.; Turner, R. Eugene
Abstract: Coastal marshes are important carbon sinks facing serious threats from climatic stressors. Current research reveals that the growth of individual marsh plants is susceptible to a changing climate, but the responses of different marsh systems at a landscape scale are less clear. Here, we document the multi‐decadal changes in the phenology and the area of the extensive coastal marshes in Louisiana, USA, a representative of coastal ecosystems around the world that currently experiencing sea‐level rise, temperature warming, and atmospheric CO2 increase. The phenological records are constructed using the longest continuous satellite‐based record of the Earth's ecosystems, the Landsat data, and an advanced modeling technique, the nonlinear mixed model. We find that the length of the growing seasons of the intermediate and brackish marshes increased concomitantly with the atmospheric CO2 concentration over the last 30 years, and predict that such changes will continue and accelerate in the future. These phenological changes suggest a potential increase in CO2 uptake and thus a negative feedback mechanism to climate change. The areas of the freshwater and intermediate marshes were stable over the period studied, but the areas of the brackish and saline marshes decreased substantially, suggesting ecosystem instability and carbon storage loss under the anticipated sea‐level rise. The marshes' phenological shifts portend their potentially critical role in climate mitigation, and the different responses among systems shed light on the underlying mechanisms of such changes. Abstract : This study documents the multi‐decadal changes in the phenology and the area of the extensive coastal marshes in Louisiana, USA, a representative of coastal ecosystems around the world that currently experiencing sea‐level rise, temperature warming, and atmospheric CO2 increase. We find that the length of the growing seasons of the intermediate and brackish marshes increased concomitantly with the atmospheric CO2 concentration over the last 30 years and predict that such changes will continue and accelerate in the future. The phenological changes of the marshes suggest a potential increase in CO2 uptake and thus a negative feedback mechanism to climate change, but the area decrease suggests ecosystem instability and carbon storage loss under the anticipated sea‐level rise. The marshes' phenological shifts portend their potentially critical role in climate mitigation, and the different responses among systems shed light on the underlying mechanisms of such changes.